Efficacy of bubaline blood derived fibrin glue in silk ligature-induced acute periodontitis in Wistar rats - Poranee Banyatworakul; Nopadon Pirarat; Sujin Sirisawadi; Thanaphum Osathanon; Chanin Kalpravidh (Veterinary World, 2021)
Background and Aim: Fibrin forms in the coagulation process, enhancing local hemostatic properties and promoting wound healing. The study aimed to evaluate the efficacy of bubaline-derived fibrin glue in silk ligature-induced periodontitis rats.